2014
DOI: 10.5603/fhc.2014.0017
|View full text |Cite
|
Sign up to set email alerts
|

The glycomic profile of invasive ductal carcinoma of the breast is altered in patients with hypoxic regions: implications for tumor behavior

Abstract: Hypoxic areas in solid tumors are often associated with poor prognosis and resistance to chemotherapy. The aim of the study was to analyze the expression of galectin-1 (Gal-1), galectin-3 (Gal-3), sialic acid and b1-6 branched glycan structures in hypoxic environment of invasive ductal carcinoma (IDC) of the breast. We performed lectin histochemistry with phytohemagglutinin-L (L-PHA) and Sambucus nigra lectin (SNA); and immunohistochemistry for Gal-1, Gal-3, carbonic anhydrase IX, hypoxia-inducible factor, est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…We also observed that Gal-1 expression was found mainly in the extracellular matrix and tumor-associated stromal cells, demonstrating their importance in the relationship between a tumor and its microenvironment [226, 227]. …”
Section: Hypoxia Alters Cell Location Of Galectins and Interaction Wimentioning
confidence: 96%
“…We also observed that Gal-1 expression was found mainly in the extracellular matrix and tumor-associated stromal cells, demonstrating their importance in the relationship between a tumor and its microenvironment [226, 227]. …”
Section: Hypoxia Alters Cell Location Of Galectins and Interaction Wimentioning
confidence: 96%
“…In general, it has been shown that the main role of galectin-1 in cancer progression represents its immunosuppressive effect, which facilitates pro-tumorigenic microenvironment [145,146] and stimulates angiogenesis [147]. Similarly, over-expression of galectin-3 in hypoxic breast tumors was associated with the presence of more aggressive tumors leading to a poor prognosis [148,149]. Galectin-3 is also an important mediator of VEGF- and bFGF-mediated angiogenic response [150].…”
Section: Antiangiogenic Effect Of Soy Isoflavonoidsmentioning
confidence: 99%
“…Zeng et al (2007) também mostraram que HIF-1α regula a expressão de galectina-3 no disco intervertebral de ratos através da interação com elementos responsivos à hipóxia (HRE -hypoxia response elements) presentes na região promotora do gene dessa lectina. Além disso, altos níveis de expressão de galectina-3 foram relacionados com áreas de hipóxia in vivo em carcinomas mamários, tanto para o subtipo carcinoma ductal in situ (REGO, et al, 2013) como para o carcinoma ductal invasivo (REGO, et al, 2014). Em nosso laboratório, também se observou a colocalização in vivo por imunoistoquímica de galectina-3 em áreas de pseudopaliçada em modelo de glioblastoma humano, sendo estas descritas como áreas hipercelulares organizadas ao redor de ambientes necróticos e, portanto, hipóxicos.…”
Section: A Fração De Células Galectina-3 Negativas Se Mantém Ao Longounclassified